A History of the Distance Library Services Conference - Peters, Timothy; Dickinson, Thad E. (Journal of library & information services in distance learning, 2020)
The Distance Library Services Conference was founded in 1982 by the librarians of the Off-Campus Library Services department at Central Michigan University. From its inception through its 18 th conference in 2018, Central Michigan University planned and administered this conference for the benefit of librarians serving distance learners and faculty at their institutions. This article discusses the founding of the Distance Library Services Conference and its role as the library profession's preeminent forum for the exchange of ideas on the topic of distance librarianship.